Study guides

☆☆

Q: What is the solution of 2y-x equals 6 y equals x plus 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2y + 2xy' + 4y + 4xy' = 0 6y + 6xy' = 0 y' = -y/x

The solution is (x, y, z) = (2.5, 1, 2.5).

x = -6

y = 6

60j + 2z = 6

Related questions

2y + 2xy' + 4y + 4xy' = 0 6y + 6xy' = 0 y' = -y/x

The solution is (x, y, z) = (2.5, 1, 2.5).

Y=-6

X = 6

x = -6

y = 6

60j + 2z = 6

The solution: x = 6/7 and x = -1

[x + y = 6] has an infinite number of solutions.

The value of c is 6

I hope you mean "What is the solution for the problem 5R plus 6 equals 36". In that case 5R + 6 = 36 5R = 36 - 6 5R = 30 R = 6

It's a simple example of addition.The solution looks like this:10 + 9 + 7 + 6 + 6 + 6 + 5 = 49

People also asked